2015
DOI: 10.1186/s12879-015-1273-5
|View full text |Cite
|
Sign up to set email alerts
|

A considerable proportion of CRF01_AE strains in China originated from circulating intrasubtype recombinant forms (CIRF)

Abstract: BackgroundIn this study, the prevalence of HIV-1 CRF01_AE intrasubtype recombinants in China is estimated and their contributions to the epidemic are explored.MethodsAvailable HIV-1 complete genomes of CRF01_AE were retrieved from the HIV database. The two alignments were evaluated with RDP3. Recombinants were defined as cases in which the recombination signal was supported by at least 3 methods with P-values of ≤0.05 after Bonferroni correction for multiple comparisons implemented in RDP3. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The 4 th is the exclusion of intersubtypic recombination, whether the components were classified or not (22, 25). The reason is that compared to nucleotide substitution, recombination can dramatically change the content of genome and confuse the phylogenetic relationship (37, 38). To investigate whether the recombination events exist among the potential LTR references and the clinical sequences, RDP4 recombination analysis tool was used to perform systematic recombination analysis (39).…”
Section: Methodsmentioning
confidence: 99%
“…The 4 th is the exclusion of intersubtypic recombination, whether the components were classified or not (22, 25). The reason is that compared to nucleotide substitution, recombination can dramatically change the content of genome and confuse the phylogenetic relationship (37, 38). To investigate whether the recombination events exist among the potential LTR references and the clinical sequences, RDP4 recombination analysis tool was used to perform systematic recombination analysis (39).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed recombination analysis is performed as previously described [ 14 17 , 43 , 46 ]. Both the jpHMM and recombination detection program (RDP4) used in the current work take the circularity of the HBV genomic sequences into consideration and can facilitate accurate predictions of recombination breakpoints even close to the 5′or 3′end of the linearized sequence [ 21 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the recombination mechanism and rate estimated, recombination of HIV-1 takes place during reverse transcription. [4][5][6]9 Thus, no recombination evidence suggested that recombination between these highly similar quasispecies is under the sensitivity of RDP4 test. The major limitation of the present study is low time resolution and small gene segments.…”
Section: Quasispecies Diversity During Primary Hiv Infectionsmentioning
confidence: 99%
“…Both intertype recombination and intratype recombination can cause serious epidemics. 8,9 High frequency of mutation and recombination during HIV reverse transcription creates fresh genetic diversity within a host. This is subject to selection pressures from the immune response and antiretroviral treatment.…”
mentioning
confidence: 99%